Pengembangan Evaluasi Berbasis Game Edukatif Blooket Pada Materi Luas Persegi Dan Persegi Panjang Pada Peserta Didik Kelas IV SD - Cindy Putri Widyawati; Naya Amelia Wibowo; Yohanes Anando Aryo; Putri Zudhah Ferryka (CV. ITTC INDONESIA, 2025)
Abstract This study aims to develop an educational game–based assessment instrument using Blooket for the topic of the area of squares and rectangles and to analyze its validity, practicality, and effectiveness in fourth-grade mathematics learning. The research employed a Research and Development (R&D) design using the 4D model, consisting of the stages of define, design, develop, and disseminate (limited implementation). The assessment product was developed using the Fishing Frenzy mode on the Blooket platform and was tested on 20 fourth-grade students. Data were collected through expert validation, observation, and field trials.The results indicate that the developed assessment instrument meets the criteria of validity, as shown by expert evaluations regarding the alignment between indicators, content, and learner characteristics. In terms of practicality, the assessment was implemented effectively even without individual devices, as the teacher only needed to display the game through a projector and call students forward sequentially to answer questions. The automatic scoring system in Blooket also facilitated efficient score recording. Regarding effectiveness, the game-based assessment successfully increased students’ motivation, focus, and confidence in answering questions. The Fishing Frenzy mode created an interactive and enjoyable classroom atmosphere, helping students understand the concept of area more optimally.Despite these positive outcomes, several challenges were encountered, including extended evaluation time due to the turn-based system, students’ limited familiarity with digital game media, and the need for more intensive classroom management. Overall, the study concludes that the Blooket-based educational game assessment is feasible, innovative, and effective for use in elementary mathematics learning.